An Annotated Translation of Sharon M Draper’s Out of My Mind - Tambunsaribu, Gunawan (Universitas Gunadarma, 2014)
This research is an annotated translation which is entitled An Annotated Translation of Sharon M Draper’s Out of My Mind. The object of the research is an English novel titled Out of My Mind. The purposes of this research are: 1) to attain factual information concerning the problems faced by the translator/researcher in translating the source text and 2) to give plausible solutions to the difficulties he encountered. In conducting this annotated translation research, the researcher employed the introspective and retrospective method. There are 25 aspects of language that analyzed by the researcher. Those difficulties were at the same time problems for the researcher. To solve the difficulties, the researcher employed some strategies such as direct translation, descriptive translation, naturalization, paraphrasing, explicitation, implication, cultural filtering, loan word, shift and many more. The researcher identified 100 items of data and annotated 25 items and the result and analysis revealed that there were 11 out of 25 data using syntactic strategy, 9 data out of 25 using pragmatic strategy, and 5 out of 25 data using semantic strategy. From twenty-five data he analyzed, the translator found that his translation contains 7 out of 25 data using form principle; 7 out of 25 data using meaning principle; 6 out of 25 data using idiom principle; and 5 out of 25 data using source language influence principle.Key words: annotation, introspective, retrospective, translation.